The Donme Jewish converts, Muslim revolutionaries, and secular Turks - Baer, Marc David (Stanford University Press, 2010)
This is the first study of the modern history, experience, and ethno-religious identity of the Doenme, the descendants of seventeenth-century Jewish converts to Islam, in Ottoman and Greek Salonica and in Turkish Istanbul.